INTERPRETASI MANAGEMENT DISCUSSION & ANALYSIS (MD & A) DAN KEMAMPUAN GOING CONCERN PERUSAHAAN - Mirna Faradisa Naurita (Jurnal Ekonomi dan Bisnis Airlangga, 2018)
Introduction: The purpose of this study is to analyze the information of MD & A to assess the ability of going-concern companies. This study uses the Indonesian pharmaceutical company,there is PT Kimia Farma (Persero) Tbk and PT Kalbe Farma as a comparison of how the MD&A for the state owned companies and private companies. Methods: Analysis of this information using the 4 aspects of MD&A includes strategic analysis, accounting analysis, financial analysis, and prospective analysis and stock market reaction shows. Results: The results of this study show that MD & A on PT Kimia Farma disclosed fully and openly, while PT Kalbe Farma is not. Conclusion and suggestion: This can lead to the existence of information asymmetry by the management to the user. Therefore the MD & A is important because provides a warning about the significant risks and help avoid risk when making investment decisions.